Giving Gifts To Employees: Review of Islamic Law and Law of the Republic of Indonesia Number 20 of 2001 - Ilgafur Tanjung (AT-TAFAHUM: Journal of Law, 2018)
As is common with gifts given to officials/employees, the giver's intention cannot be separated from one of two things, namely the gift giver aims to win the favor of the official/employee so that they get convenience and relief in all their affairs both at that time and in the future. The gift giver who does give it out of affection and does not expect any reward, either material or services. In this problem, the author emphasizes the perspective of Islamic law and Law No. 20 of 2001 concerning the law of gifts given to officials and the conditions that allow officials to receive gifts. The results of the research from this discussion are gifts given to officials/employees because of their work and position are forbidden for both the giver and the recipient as prohibited by Islam and the law. The basis for the prohibition and impermissibility of these gifts is the failure to realize equal rights between fellow human beings, both individual and social. As for gifts given to employees/officials not because of their work and position, then the law is permissible for both the giver and the recipient. Especially if the giver intends to strengthen ties of kinship and strengthen relationships between each other.